2012
DOI: 10.1038/npp.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Stress-Impaired Fear Extinction Through Neuropeptide S Action in the Lateral Amygdala

Abstract: Stressful and traumatic events can create aversive memories, which are a predisposing factor for anxiety disorders. The amygdala is critical for transforming such stressful events into anxiety, and the recently discovered neuropeptide S transmitter system represents a promising candidate apt to control these interactions. Here we test the hypothesis that neuropeptide S can regulate stress-induced hyperexcitability in the amygdala, and thereby can interact with stress-induced alterations of fear memory. Mice un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 68 publications
(90 reference statements)
5
76
1
Order By: Relevance
“…Our data is consistent with the finding that NPSR mRNA is widely distributed in the BLA in mice . In addition, local infusion of NPS into lateral/basolateral amygdala is demonstrated to facilitate extinction of conditioned fear memory, and NPS in the lateral amygdala prevents stress-induced impairment of fear extinction (Chauveau et al, 2012;Juengling et al, 2008). Present findings and previous reports suggest that amygdala is crucial for the regulatory effects of NPS on aversive and non-aversive memories.…”
Section: Discussionsupporting
confidence: 74%
“…Our data is consistent with the finding that NPSR mRNA is widely distributed in the BLA in mice . In addition, local infusion of NPS into lateral/basolateral amygdala is demonstrated to facilitate extinction of conditioned fear memory, and NPS in the lateral amygdala prevents stress-induced impairment of fear extinction (Chauveau et al, 2012;Juengling et al, 2008). Present findings and previous reports suggest that amygdala is crucial for the regulatory effects of NPS on aversive and non-aversive memories.…”
Section: Discussionsupporting
confidence: 74%
“…It is also suggested that in the rat medial amygdala, NPS stimulates GABAergic inhibitory neurons, reducing fear-related activities (Jungling et al 2008). Moreover, the NPS signaling may be involved in the regulation of HPA axis, because it acts as a part of a negative feedback loop in response to various stress stimuli (Chauveau et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Coronal slices were prepared and whole-cell patch clamp recordings were obtained from principal neurons (PNs) in the lateral amygdala (LA) (Sah et al, 2003), as described previously (Sosulina et al, 2006; for details, see Supplementary Information). After assessing membrane properties, postsynaptic responses were recorded under current-or voltage-clamp conditions, as previously described (Chauveau et al, 2012; for details, see Supplementary Information). Extracellular stimuli (500 ms duration) were delivered every 20 s through a bipolar stainless-steel electrode, placed at thalamic or cortical afferents (Szinyei et al, 2000).…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%